4-Bromo-N-cyclohexylbenzenesulfonamide - John, P.; Anwar, F.; Khan, I.U.; Sharif, S.; Tiekink, E.R.T. (International Union of Crystallography, 2010)
The title compound, C(12)H(16)BrNO(2)S, adopts an L-shaped conformation with the central C-S-N-C torsion angle being -77.8 (3)degrees. The crystal packing features N-H...O hydrogen bonds, which lead to C(4) chains propagating in [010]; the second O atom is involved in short intramolecular C-H...O contacts